Beyond yields: A systems approach is essential for reconciling agriculture and biodiversity - Beillouin, Damien; Jones, Sarah; Rapidel, Bruno; Estrada-Carmona, Natalia (Royal Society, 2025)
Balmford et al. advocate land sparing and high yields as the primary strategy to address biodiversity loss and ensure food security. We challenge the notion that managing agricultural land solely to optimize yields can halt or reverse the decline of biodiversity. Decades of yield-centric agriculture, divorced from ecological and social concerns, have proven inadequate.